Implementation of Educational Values as a Model of Academic Supports in Characters Education (A Case Study in Indonesia Education University) - Sardjiyo Sardjiyo (LPPM UNY, 2011)
The main question for this study is whether the General Course Program (GCP) contributes to the achievement of the vision, mission, and objectives of the Indonesia Education University (IEU) in order to form the personality of students through the educational value as an academic support of Character Education. This study applied the qualitative research method involving lecturers, students, and officials of IEU as the research respondents. Techniques of data collection were in-depth interviews with the respondents from the five schools of Education, Mathematics and Physical Sciences, Languages and Arts, Sports and Health, and Engineering. The study findings suggest that GCP contribute greatly to the formation of personality of students through values education as an academic support of character education as stated in the content of the course materials. More specifically, values are not explicitly emphasized in each of the lecture but are integratedly loaded in the course materials; the role of lecturers is to further reinforce the application of values in everyday life; the GCP contributes to giving the strengthening of values as academic support; some lecturers are not as much concerned with the personality development of students but just looking for survivals for themselves.